Associations between unhealthy dieting behaviors and tobacco use among adolescents - Sutter, Megan E. (J Eat Disord, 2016)
BACKGROUND: Cigarette smoking is an important risk factor for unhealthy dieting behaviors (UDBs) in youth. The role of alternative tobacco products and UDB engagement has yet to be examined empirically despite concerning trends in use. This study aimed to examine UDB prevalence in a U.S. geographic region-specific adolescent sample and associations with a variety of tobacco use behaviors and perceptions. METHODS: Weighted data from the 2013 Virginia Youth Survey were analyzed (n = 6903). UDBs assessed included past 30-day fasting, diet pill use, and vomiting/laxative use. Tobacco-related items were ever and past 30-day cigarette smoking, past 30-day smokeless tobacco and cigar use, and the perception that smokers have more friends. UDB prevalence was recoded by the number of behaviors endorsed (0, 1, and 2+). Bivariate and multinomial regression models were used to examine associations between covariates and number of UDBs endorsed by gender. RESULTS: Overall, nearly 16% engaged in at least one UDB. Fasting was most prevalent (14.2%) followed by vomiting/laxative (7.0%) and diet pill use (6.1%). Across gender, ever cigarette smoking, past 30-day cigar use, and the perception that smokers have more friends were positively associated with UDB engagement in relative isolation as well as in combination. CONCLUSIONS: Findings highlight the importance of tobacco-related factors for weight control behaviors and are the first to identify an association between UDB incidence and an alternative tobacco product, cigars. This work should inform prevention efforts for tobacco use and UDBs and underscores the need to address the use of any tobacco for weight control.